Meta‐Analysis of Gut Dysbiosis in Parkinson's Disease - Nishiwaki, Hiroshi; Ito, Mikako; Ishida, Tomohiro; Hamaguchi, Tomonari; Maeda, Tetsuya; Kashihara, Kenichi; Tsuboi, Yoshio; Ueyama, Jun; Shimamura, Teppei; Mori, Hiroshi; Kurokawa, Ken; Katsuno, Masahisa; et al. (Movement disorders, 2020)
Background PD may begin with the intestinal accumulation of α‐synuclein fibrils, which can be causally associated with gut dysbiosis. The variability of gut microbiota across countries prevented us from identifying shared gut dysbiosis in PD. Objectives To identify gut dysbiosis in PD across countries. Methods We performed 16S ribosomal RNA gene sequencing analysis of gut microbiota in 223 patients with PD and 137 controls, and meta‐analyzed gut dysbiosis by combining our dataset with four previously reported data sets from the United States, Finland, Russia, and Germany. We excluded uncommon taxa from our analyses. For pathway analysis, we developed the Kyoto Encyclopedia of Genes and Genomes orthology set enrichment analysis method. Results After adjusting for confounding factors (body mass index, constipation, sex, age, and catechol‐O‐methyl transferase inhibitor), genera Akkermansia and Catabacter, as well as families Akkermansiaceae, were increased, whereas genera Roseburia, Faecalibacterium, and Lachnospiraceae ND3007 group were decreased in PD. Catechol‐O‐methyl transferase inhibitor intake markedly increased family Lactobacillaceae. Inspection of these bacteria in 12 datasets that were not included in the meta‐analysis revealed that increased genus Akkermansia and decreased genera Roseburia and Faecalibacterium were frequently observed across countries. Kyoto Encyclopedia of Genes and Genomes orthology set enrichment analysis revealed changes in short‐chain fatty acid metabolisms in our dataset. Conclusions We report that intestinal mucin layer‐degrading Akkermansia is increased and that short‐chain fatty acid–producing Roseburia and Faecalibacterium are decreased in PD across countries. © 2020 International Parkinson and Movement Disorder Society